Protective effects of Indigofera argentea against acetic acid-induced inflammatory bowel disease are mediated by modulating antioxidant and inflammatory mediators - Faraza Javaid; Qaiser Jabeen (Avicenna Journal of Phytomedicine)
Objective: The plant Indigofera argentea Burm. f., belonging to the family Fabaceae, is locally known as Hathio, Jantar and Neel. This plant is commonly found in deserted habitat and used traditionally to treat inflammatory and gastric disorders.  The current study was designed to evaluate the phytochemical profile, toxicity and intestinal anti-inflammatory effects of the whole plant crude extract against acetic acid-induced inflammatory bowel disease (IBD) in mice.Materials and Methods: To study the phytochemical composition, preliminary phytochemical analysis along with HPLC and LCMS of the crude extract of Indigofera argentea (Ia.Cr) was performed. For the evaluation of intestinal anti-inflammatory activity, animals were divided into five groups (normal control, intoxicated, standard and two treatment groups) of six animals each and ulcerative colitis (UC) was induced by intrarectal administration of acetic acid (200 µl of 7.5%) and extent of damage caused by ulcerative colitis was measured by colonic mucosal damage index, disease activity index, and hematological and histological changes. Lipo-peroxide activity by malondialdehyde (MDA) and antioxidant enzyme glutathione peroxidase (GPX-1), catalase (CAT) and superoxide dismutase (SOD) levels were determined in colon tissues. Pro-inflammatory cytokines (IL-1, IL-6 and TNF-α) were quantified by ELISA immunoassay.Results: Pre-treatment with Ia.Cr significantly amended macroscopic damage, and hematological and histopathological alterations. Ia.Cr decreased oxidative parameters such as MDA and increased antioxidant activities of GPX-1, CAT and SOD. Ia.Cr also decreased the levels of pro-inflammatory biomarkers significantly.Conclusion: Results of this study indicated that Ia.Cr protected mice against acetic acid-induced inflammatory bowel disease by decreasing endogenous inflammatory biomarkers and oxidative damages.